Is there no women in investment? - Carolin Dylla; Dorothea Ries; Karolina Schütt (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
As European pension systems are struggling to provide financial security in retirement under the pressure of demographic change, poverty in old age disproportionally affects women. Given these developments, private investment is becoming ever more important to securing financial means after retirement. Therefore, this paper investigates which factors determine female and male investment behaviour in Germany regarding different asset classes? It is hypothesised that (i) differences in investment behaviour are mainly driven by wealth and income. (ii) However, even after controlling for income, there are still gender differences in investment behaviour. We conduct a thorough literature review and empirical analysis based thereon, using the 2017 data wave of the ECB's Household Finance and Consumption Survey (HFCS) for German single households. Controlling for selected socio-economic variables, we find that women have significantly less holdings in risky assets. This observation holds even when adding gross household income as further control variable. However, no difference between male and female investment behaviour can be detected in relatively risk-free asset classes. The findings in this paper contribute to existing and future research - its literature points out the ambiguity and lack of coherence in existing research in the topic of gendered investment behaviour. Further, its empirical analysis provides new insights using the updated 2017 HFCS dataset, with most previous research based on 2010/14 HFCS data. Lastly, we are drawing attention to the unequal strategies of wealth accumulation between men and women and their ramifications for wealth distribution providing important contextualisation for future policy-making.
Keywords: D31; G11; J16; 330; Gender; Inequalities; Finance; Portfolio Choices; Assets; HFCS